RETAINED SURGICAL SPONGE IN A DOG: CLINICAL ASPECTS AND SURGICAL APPROACH - Liviu Cătălin BURTAN; Alexandra CIUBOTARIU (Journal of Applied Life Sciences and Environment)
Although retained surgical sponges are rarely reported, their clinical aspect can sometimes vary and therefore, the diagnosis can be challenging. An eight-year-old mixed breed dog was brought in for a skin lesion on the lateral abdominal wall that appeared nine weeks previously, which could not be treated even though both local and general therapy had been carried out. During antibiotic administration, the dog’s condition improved, but once the treatment was completed, the wound and secretions started to reappear. Diagnosis of a retained surgical gauze was based on history, clinical signs, radiological examination and confirmed by surgical exploration. This article aims to describe the clinical and surgical findings of this pathology, which appeared four years after the surgical procedure, in order to disseminate knowledge about the complications that may occur if negligence, disorganisation or lack of emergency protocols exists.